Legal consequences of the invalidity of a transaction made by using information technology: problems of theory and practice - Давидова, Ірина Віталіївна; Давидова, І. В.; Давыдова, Ирина Виталиевна; Davydova, Iryna V.; Орзіх, Юрій Геннадійович; Орзіх, Ю. Г.; Орзих, Юрий Геннадиевич; Orzikh, Yurii H.; Самойленко, Георгій Валерійович; Самойленко, Г. В.; Самойленко, Георгий Валерьевич; Samoylenko, Georigiy V.; et al. (Universidad de la Amazonia, 2019)
The article deals with the problem of determination of the peculiarities of legal consequences of invalidity of transactions committed with the use of modern information technologies. The authors believe that the development of modern information technologies has led to the emergence of «new» and «transitional» transactions. The object of the study is completely «new» transactions (for example, IT-transactions that are concluded on the Internet, including using the Blockchain technology) and «transitional transactions», which are only partially different in form and/or manner than traditional ones (for example, electronic transactions, transactions where the object is related to the IT-environment, etc.). As to the consequences of the recognition of transactions invalid, then, in the opinion of the authors, the basis is to take the general model of recognition of invalid transactions, which provides for restitution and compensation for damage. Particular attention should be paid to the recognition of invalid IT-transactions to the «a priori validity» of such transactions, which can create significant risks for users of the blockade software platform and make it difficult to protect their rights in the future. The results obtained is seen in the creation of a new concept of the law in the information society with the development of an appropriate legal mechanism for the protection of the rights of their participants, in particular, the concept of the invalidity of IT-transactions and their legal implications.

У статті розглянуто проблему визначення особливостей правових наслідків недійсності правочинів, вчинених із застосуванням сучасних інформаційних технологій. Автори вважають, що розвиток сучасних інформаційних технологій призвів до появи «нових» і «перехідних» транзакцій. Об’єктом дослідження є повністю «нові» транзакції (наприклад, ІТ-транзакції, що укладаються в Інтернеті, в тому числі за допомогою технології Blockchain) та «перехідні транзакції», які за формою та/або способом лише частково відрізняються від традиційних. (наприклад, електронні транзакції, операції, де об'єкт пов'язаний з ІТ-середовищем тощо). Щодо наслідків визнання правочинів недійсними, то, на думку авторів, за основу слід взяти загальну модель визнання правочинів недійсними, що передбачає реституцію та відшкодування шкоди. Особливу увагу слід звернути на визнання недійсними ІТ-транзакцій «апріорної чинності» таких транзакцій, що може створити значні ризики для користувачів програмної платформи блокування та ускладнити захист їхніх прав у майбутньому. Отримані результати вбачаються у створенні нової концепції права в інформаційному суспільстві з розробкою відповідного правового механізму захисту прав їх учасників, зокрема концепції недійсності ІТ-операцій та їх правові наслідки.
Davydova I. Legal Consequences of the Invalidity of a Transaction made by Using Information 'Technology: Problems of Theory and Practice / I. Davydova, Y. Orzikh, G. Samoylenko, I. Andronov, M. Pysarenko // AMAZONIA INVESTIGA. - Universidad de la Amazonia, 2019. - Vol. 8. - Issue 19. - Р. 613-619.
Keywords: IT-transactions; Blockchain; IT sphere; legal regulation; invalid transactions; legal norm; modern information technologies; restitution; IT-транзакції; блокчейн; IT сфера; правове регулювання; недійсні операції; правова норма; сучасні інформаційні технології; реституція; Research Subject Categories::LAW/JURISPRUDENCE